Ultra‐Long Lifetimes of Single Quantum Emitters in Monolayer WSe2/hBN Heterostructures. Issue 5 (1st April 2019) - Dass, Chandriker Kavir; Khan, Mahtab A.; Clark, Genevieve; Simon, Jeffrey A.; Gibson, Ricky; Mou, Shin; Xu, Xiaodong; Leuenberger, Michael N.; Hendrickson, Joshua R.
Abstract: Here, ultra‐long lifetimes of defect‐trapped single quantum emitters (SQEs) in monolayer WSe2 /hBN heterostructures are reported. The lifetimes of these SQEs are approximately 225 ns, more than two orders of magnitude larger than what has been previously reported for defect‐trapped excitons in WSe2 . These SQEs consist of co‐linearly polarized doublet peaks with a fine structure splitting of 0.45 meV. Second‐order correlation measurements show antibunched single‐photon emission with a g (2) (0) value of ≈0.13. Through numerical analysis and modeling, it is shown how such long‐lifetime single emitters can arise from bright and dark exciton coupling in antisite defects on the W sites. Additionally, high‐quality single‐photon emission over a wide range of lifetimes—from 2 ns to over 200 ns—is also reported, suggesting a variety of other possible defect structures present. The flexibility to generate high fidelity single‐photon emission, over a wide range of lifetimes in a single material system, has potential in many optical quantum computing applications from high‐bit‐rate single‐photon sources to quantum memory devices. Abstract : 2D materials are promising hosts for single quantum emitters (SQE) as the light extraction efficiencies can be much higher than thicker material platforms, but understanding the nature of these single emitter sites has been elusive. Here, it is shown that SQE lifetimes in WSe2 can be much longer than previously demonstrated due to bright and dark exciton coupling.